Optimal operation of cascaded hydropower plants in hydro-solar complementary systems considering the risk of unit vibration zone crossing - Haoting, Qin; Tianzhi, Li; Jianhua, Li; Yunxia, Wu; Hongtao, Song (Frontiers in Energy Research, 2023)
With the undergoing adjustment of the national energy structure of China, developing cascaded hydropower plants in hydro-solar complementary systems becomes an important way to optimize the energy structure. This study focuses on the risk that solar energy disturbances induce large load transfers between hydropower units that can cause hydropower units to frequently cross their vibration zones. Vibration zone crossing can further cause wear of mechanical components of hydropower units. To this end, considering the requirement of avoiding vibration zone crossing, the concept of the vibration zone crossing risk coefficient is introduced and a cascaded hydropower plant optimal operation model considering the risk of vibration zone crossing is proposed. Moreover, this is two-layer algorithm. This layer of algorithms includes improved migration model and migration operator is proposed to solve this mean a cascaded hydropower plant optimal operation model considering the risk of vibration zone crossing. Numerical simulation results based on the data of an actual hydropower plant are used to validate the proposed model and (IBBO-DP) algorithm.